A Prospective, Initiative, Single-Center Open Post-Registration Comparative Study of Laboratory Efficacy of Various Forms of Acetylsalicylic Acid in a Cardioprotective Dose with Different Composition of Excipients: Results of the SFAIROS Study - N. V. Lomakin; L. I. Buryachkovskaya; D. A. Zolin; V. I. Kazey (Рациональная фармакотерапия в кардиологии)
Aim. To compare the kinetics of dissolution (in vitro) and some pharmacodynamic and pharmacokinetic parameters of branded generic preparations of acetylsalicylic acid (ASA) in buffered form in cardioprotective doses [ASA 75 mg+Mg(OH)2 15.2 mg], which differ in the composition of excipients, with a reference drug.Material and methods. Patients with cardiovascular diseases who had indications for ASA monotherapy (n=75) were included in a one-center open postregistration comparative non-randomized study. Patients were divided into 3 groups for treatment with one of the three studied drugs: Cardiomagnyl® (comparison drug; group 1; n=25), Trombital® (group 2; n=25) and Fazostabil® (group 3; n=25). A study of the kinetics of dissolution of the studied drugs in vitro under conditions of pH 1.2 has been performed. Also, platelet aggregation in response to arachidonic acid, the concentration of salicylic acid and the level of serum thromboxane B2 were studied in the compared groups.Results. The average release profile of ASA by the 30th minute from Cardiomagnyl® was higher than for Trombital® and Fazostabil® (95.7%, 84.8%, 76.5% respectively). The similarity factor (f2) of ASA release for Trombital® was 39.3, and for Fazostabil® - 34.2. An index of f2<50 indicates a nonequivalent release of ASA compared with the reference drug. The serum level of salicylic acid 2 hours after taking the first dose of the drug in patients of group 1 was 2657.3±648.4 ng/ml, in group 2 - 2637.0±740.0 ng/ml (p=0.03) and in group 3 it was to 2632.1±666.0 ng/ml (p=0.002). The platelet aggregation after 3 days decreased and in groups 1, 2 and 3 were respectively 7.6%, 32.2% (p=0.000) and 16.3% (p=0.009). Differences in the disaggregation effect between the groups persisted by the 7th day of the study (7.9%, 9.1% and 20.5% respectively; p=0.04 for the latter). The thromboxane B2 level by the 3rd day of administration decreased compared to the initial level in group 1 to 15.5%, in group 2 to 21.1% and in group 3 to 20.0% (p=0.05 for both). The trend persisted by the 7th day.Conclusion. The pharmacodynamic and pharmacokinetic parameters of the studied drugs differed statistically significantly with the advantage for the comparison drug despite the same active substance.